Human Rights Violation in Africa: A Critical Assessment of Rule of Law in Nigeria - NWOSU, Ikechukwu Jude Donald (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2024)
The discourse about human rights violations has been a recurrence among scholars in Africa. This is because the lives of the African citizens particularly the Nigerians are been decimated and harassed on daily basis through nefarious acts. A bid to find out the magnitude of violation of human rights in Nigeria necessitated this study. Its central focus is to critically assess how rule of law in Nigeria has addressed human rights violations among the citizens. The study further ascertained the nature and level of violation of human rights amongst the citizens of Nigeria. The paper was anchored on both historical and analytical, as facts and figures were gathered from secondary sources using the content analysis method. Judging from the theoretical underpinning of this study, the Social Contract Theory of State stipulates that the rule of law is very important to human existence as it helps to regulate citizens’ actions and make them live harmoniously with each other as without the presence of law, it will be impossible if not difficult for the citizens to get access to basic amenities of life. It was observed that the failure to strictly adhere to the principles of rule of law has resulted in human rights violations which are evident in violation of the right to life, freedom of expression among others. It was therefore concluded that the principle of rule of law if imbibed and practised irrespective of social status, religion or ethnic grouping will engender a peaceful and harmonious nation.